Out-of season induced spawning of the Cyprinus carpio in Basra-Iraq - Jabir, A.A.; Al- Mukhtar, M. A.; AL-Zaedy, F.M.; Saleh, J. H.; Hassan, A. M. (Iraqi Journal of Aquaculture, 2022)
The out-of season induced spawning of the Cyprinus carpio was done during the period October 2009 to February 2010 (Autumn and Winter), in the hatchery of Marin Science Center. The brooders average weight was 1.700-4.000 kg for females and 1.500-1.800 kg for males. The brooders were acclimated on 22 °C, for a period of 10 days. The photoperiod was 12-14 hour/day. The results showed that in this regime only one female and 3males had positive reaction to the pituitary gland hormone injection. While 4 female were positive to the Ovaprim during the second regime, in which the brooders were acclimated for 25 days, with same temperature and photoperiod. It was seen that the thermal acclimation for a long period out-of season was better for the maturation and spawning, and the use of Ovaprim give more response than PG extract. The indoor rearing of the larvae gives average weight of 0.5 g after 6 weeks. These results means that we can produce the fry of common carp before one month prior to the usual spawning season, which will prolong the production season in Basra Province.